2022
DOI: 10.1002/bbb.2400
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced enzymatic hydrolysis of corn stover using twin‐screw extrusion under mild conditions

Abstract: This paper aims to investigate the effect of extrusion at high solid loading on corn stover (CS) properties and its enzymatic hydrolysis. This biomass was extruded under different screw speeds and different solid loadings and the impact of these parameters on the physicochemical properties was evaluated. It was found that lignocellulosic components were not significantly affected by the pretreatment, while the surface area increased with solid loading and rotation speed. Different enzyme cocktails were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Finally, in the case of rehydrated corn stover, which was mechanically treated with a twin-screw extruder, Wang et al [55] showed a slight increase for cellulose (1%), and slight decreases for hemicelluloses (1%) and, especially, lignin (0.2%) contents. Lastly, in their very recent study, Elalami et al [56] showed no statistical difference in the chemical composition of corn stover before and after extrusion. In conclusion, although HE/HER configuration allowed partial solubilization of extractables, which significantly impacted the extrudate's composition in lignocellulosic compounds from a statistical point of view, mechanical extrusion only slightly altered the biomass lignocellulosic composition.…”
Section: Effect Of the Twin-screw Extrusion Mechanical Pretreatment O...mentioning
confidence: 90%
“…Finally, in the case of rehydrated corn stover, which was mechanically treated with a twin-screw extruder, Wang et al [55] showed a slight increase for cellulose (1%), and slight decreases for hemicelluloses (1%) and, especially, lignin (0.2%) contents. Lastly, in their very recent study, Elalami et al [56] showed no statistical difference in the chemical composition of corn stover before and after extrusion. In conclusion, although HE/HER configuration allowed partial solubilization of extractables, which significantly impacted the extrudate's composition in lignocellulosic compounds from a statistical point of view, mechanical extrusion only slightly altered the biomass lignocellulosic composition.…”
Section: Effect Of the Twin-screw Extrusion Mechanical Pretreatment O...mentioning
confidence: 90%